THE ROLE OF THE PRINCIPLE OF OPERATION OF A NEURAL NETWORK IN SOCIETY (Modern education and development, 2025)
This article analyzes the working principle of neural networks and their role in society. Neural networks, as a key component of artificial intelligence and machine learning technologies, are revolutionizing many fields. The working principle of the network is based on the human brain, capable of learning, classifying, and making decisions based on data. It is effectively used in production optimization, medical diagnostics, creating personal assistants, and automation systems. The article also discusses the economic and social impact of neural networks on society, ethical issues, and future development prospects.